Hubungan Self Efficacy Terhadap Minat Mengajar : Studi Pada Mahasiswa Pendidikan Akuntansi - Ully Atika; Dian Novianti Sitompul (Faculty of Teacher Training and Education of Undaris, 2026)
This study aims to reveal the relationship between self-efficacy and teaching interest in AccountingEducation students at the University of Muhammadiyah North Sumatra (UMSU). Self-efficacy is anindividual's belief in their ability to complete tasks or face certain situations, which is believed to have aninfluence on students' readiness and interest in pursuing a profession as an educator. The researcher used aquantitative approach with a survey design. The population in this study were all 98 accounting educationstudents at UMSU and the sample was the entire population. The sampling technique used was totalsampling. The research instrument used a questionnaire. The data analysis technique used simple linearregression analysis with the help of SPSS 23 software. The results of the statistical analysis showed a positiveand significant relationship between self-efficacy and teaching interest of 39.5%. This means that the higherthe level of student self-efficacy, the greater their interest in becoming a teacher.Keywords: Self-efficacy, Teaching Interest